Engineering hyaluronic acid-based nanoassemblies for monoclonal antibody delivery – design, characterization, and biological insights - López Estévez, Ana M. (2024)
The current spotlight of cancer therapeutics is shifting towards personalized medicine with the widespread use of monoclonal antibodies (mAbs). Despite their increasing potential, mAbs have an intrinsic limitation related to their inability to cross cell membranes and reach intracellular targets. Nanotechnology offers promising solutions to overcome this limitation, however, formulation challenges remain. These challenges are the limited loading capacity (often insufficient to achieve clinical dosing), the complex formulation methods, and the insufficient characterization of mAb-loaded nanocarriers. Here, we present a new nanocarrier consisting of hyaluronic acid-based nanoassemblies (HANAs) specifically designed to entrap mAbs with a high efficiency and an outstanding loading capacity (50%, w/w). HANAs composed by an mAb, modified HA and phosphatidylcholine (PC) resulted in sizes of ~ 100 nm and neutral surface charge. Computational modeling identified the principal factors governing the high affinity of mAbs with the amphiphilic HA and PC. HANAs composition and structural configuration were analyzed using the orthogonal techniques cryogenic transmission electron microscopy (cryo-TEM), asymmetrical flow field-flow fractionation (AF4), and small-angle X-ray scattering (SAXS). These techniques provided evidence of the formation of core-shell nanostructures comprising an aqueous core surrounded by a bilayer consisting of phospholipids and amphiphilic HA. In vitro experiments in cancer cell lines and macrophages confirmed HANAs’ low toxicity and ability to transport mAbs to the intracellular space. The reproducibility of this assembling process at industrial-scale batch sizes and the long-term stability was assessed. In conclusion, these results underscore the suitability of HANAs technology to load and deliver biologicals, which holds promise for future clinical translation.